Stocking African catfish in Lake Victoria provides effective biocontrol of snail vectors of Schistosoma mansoni - Proud, Roland; Allan, Fiona; Whiston, Andrew; Kayanda, Robert; Kinung’hi, Safari; Angelo, Teckla; Sylivester, Yasinta D.; Mrosso, Hillary D. J.; Kashindye, Benedicto B.; Elison, Mboni; Cox, Martin J.; Yang, Yang; et al. (PLOS Neglected Tropical Diseases, 2025)
In areas of high infection prevalence, effective control of schistosomiasis – one of the most important Neglected Tropical Diseases – requires supplementing medical treatment with interventions targeted at the environmental reservoir of disease. In addition to provision of clean water, reliable sanitation, and molluscicide use to control the obligate intermediate host snail, top-down biological control of parasite-competent snails has recently gained increasing interest in the scientific community. However, evidence that natural predators can effectively reduce snail abundance and, ultimately, transmission risk to vulnerable human populations remains limited. In this study, we used a Before-After-Control-Intervention (BACI) design implemented in seven lakeside areas, including three intervention areas and four control areas, on the southern shores of Lake Victoria (Tanzania) in 2019–2023. We tested whether the restoration of African catfish, Clarias gariepinus, a native species of commercial value, could reduce both the abundance of Biomphalaria snails (intermediate hosts of Schistosoma mansoni) and infection intensity in school age children (SAC). Where catfish were restored, mean site-level snail counts declined by 57% (95% CI: 29.4%, 74.3%). At primary schools located within each area, SAC infection intensity (mean parasite egg count in stool samples) also decreased significantly by 55% (95% CI: 26%, 73%). This study shows that natural predators of host snails have the potential for schistosomiasis control. Scaling up to a lake-wide approach will require systemic intervention, with snail host control contributing to a broader framework for schistosomiasis management.